PENGUATAN LIMA MODAL LIVELIHOOD MELALUI UMKM OLAHAN SUSU: ANALISIS SUSTAINABLE LIVELIHOODS FRAMEWORK - Abdullah Shofa (Dinamika Sosial: Jurnal Pendidikan Ilmu Pengetahuan Sosial, 2025)
This study analyzes the contribution of the i-SuKa dairy-based MSME in strengthening the five livelihood capitals within the framework of the Sustainable Livelihoods Framework (SLF) in Ngabab Village, Malang Regency. A descriptive qualitative method was applied through observation, interviews (10 informants), and document analysis. The results indicate contributions through technical skills, the institutional role of the Joint Business Group (KUB), production facilities, employment absorption, and the utilization of natural resources. The main challenges include limited digital literacy, manual packaging technology, restricted access to capital, and vulnerability to climate and livestock diseases. Key findings reveal dynamic interconnections among livelihood capitals, where weaknesses in one capital hinder the optimization of others. Comparatively, the findings align with Smith et al. in Thailand regarding digital literacy constraints; however, training policies in Indonesia remain unstructured. Meanwhile, technological limitations parallel those identified by Patel and Kumar in India, yet differ in the complexity of financing access. Policy implications emphasize KUB-based digital training, access to technology financing, and integrated risk management. The study concludes that SLF provides a holistic perspective and contextual relevance through comparative analysis. ABSTRAK Kontribusi orisinal Penelitian ini adalah menganalisis kontribusi UMKM olahan susu i-SuKa dalam memperkuat lima modal livelihood berbasis Sustainable Livelihoods Framework (SLF) di Desa Ngabab, Kabupaten Malang. Metode kualitatif deskriptif diterapkan melalui observasi, wawancara (10 informan), dan studi dokumentasi. Hasil menunjukkan kontribusi melalui keahlian teknis, Kelembagaan KUB, fasilitas produksi, penyerapan tenaga kerja, dan pemanfaatan SDA. Tantangan utama meliputi literasi digital terbatas, teknologi pengemasan manual, akses modal terbatas, serta kerentanan iklim dan penyakit ternak. Temuan kunci mengungkap interkoneksi dinamis antar modal, dimana kelemahan satu modal menghambat optimalisasi modal lain. Secara komparatif, temuan selaras dengan studi Smith et al. di Thailand tentang kendala literasi digital, namun kebijakan pelatihan di Indonesia belum terstruktur. Sementara, keterbatasan teknologi sejalan dengan Patel dan Kumar di India, namun berbeda dalam kompleksitas akses pembiayaan. Implikasi kebijakan menekankan pelatihan digital berbasis KUB, akses pembiayaan teknologi, dan manajemen risiko terpadu. Penelitian menyimpulkan SLF memberikan perspektif holistik dan relevansi kontekstual melalui analisis komparatif.